Hubungan Antara Tingkat Aktivitas Fisik dengan Fungsi Kognitif Pada Lanjut Usia - Oktafina Safita Nisa; Arief Wahyudi Jatmiko (Universitas Muhammadiyah Surakarta, 2019)
Along with the aging process, all systems of the body dealing with changes or gradual deterioration functions, one of which was a decrease in physical activity. A decrease in physical activity in the elderly was one of the causes of cognitive impairment. Decline in cognitive function in the elderly is the biggest cause of the inability to perform normal daily activities. The purpose of the study was to know the correlation between the level of physical activity and cognitive function in the elderly in Pucangan Village Kartasura SubDistrict. This research was cross sectional design. The population were in this study are listed on the elderly Posyandu Pucangan Village Kartasura Sub-District aged >60 years and include in inclusion criteria. The total sample in this study were 95 respondents. Sampling technique used is nonprobability sampling technique with proportional sampling method. The instrument used to measure the level of physical activity is GPPAQ (General Practice Physical Activity Questionnaire) and for cognitive function using the MMSE (Mini Mental State Examination). Analys of the data used was Chi Square test. Results of univariate known that elderly people who have high levels of physical activity inactive (35.8%) and active as much (21.1%). The percentage of elderly who have normal cognitive function as many (29.5%) and those with severe cognitive disorders amounted to (43.2%). The result of bivariate analysis there was no relationship between the level of physical activity and cognitive function in which showed the value of p value = 0.010 (p> 0.05) means that Ho was rejected. The conclusions of this study shows there is a relationship between the level of physical activity and cognitive function in the elderly in Pucangan Village Kartasura Sub-District.